1996
DOI: 10.1080/10826069608000070
|View full text |Cite
|
Sign up to set email alerts
|

ε-N-Acetylation in the Production of Recombinant Human Basic Fibroblast Growth Factor Mutein

Abstract: During large scale preparation of recombinant human basic fibroblast growth factor (hbFGF) mutein CS23(CS23) produced in Escherichia coli (E. coli), three species, named Mf-1, Mf-2 and Mf-3 in the order of their elution, were isolated from the early fraction of Sulfated Cellulofine chromatography by high performence liquid chromatography (HPLC) on heparin-5pw. Structural analysis through HPLC peptide mapping, mass spectrometry, sequencing and amino acid composition revealed that epsilon-N-acetylation occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Lysine acetylation has been detected following production in E. coli of recombinant therapeutic proteins, including the chemokine RANTES (d'Alayer et al, 2007), human basic fibroblast growth factor mutein (Suenaga et al, 1996), human carbonic anhydrase (Mahon et al, 2015), insulin lispro (Szewczak et al, 2015), interleukin-10 (Pflumm et al, 1997), interleukin-2 (Moya et al, 2002), interferon alpha (Takao et al, 1987), neurotropin-3 (Ross et al, 1996), and somatotropin (Violand et al, 1994). Nearly 30% of currently approved recombinant therapeutic proteins are produced in E. coli (Huang et al, 2012).…”
Section: Consequences For Pharmaceutical Productionmentioning
confidence: 99%
“…Lysine acetylation has been detected following production in E. coli of recombinant therapeutic proteins, including the chemokine RANTES (d'Alayer et al, 2007), human basic fibroblast growth factor mutein (Suenaga et al, 1996), human carbonic anhydrase (Mahon et al, 2015), insulin lispro (Szewczak et al, 2015), interleukin-10 (Pflumm et al, 1997), interleukin-2 (Moya et al, 2002), interferon alpha (Takao et al, 1987), neurotropin-3 (Ross et al, 1996), and somatotropin (Violand et al, 1994). Nearly 30% of currently approved recombinant therapeutic proteins are produced in E. coli (Huang et al, 2012).…”
Section: Consequences For Pharmaceutical Productionmentioning
confidence: 99%
“…This modification has been demonstrated in E. coli in expressing recombinant proteins, although it has been shown that these adventitious post‐translational modifications are mostly undesirable. A recombinant human basic fibroblast growth factor mutein, expressed in E. coli , exhibited ɛ‐N‐acetylation of three lysines, although there is no apparent functionality associated with this modification (Suenaga et al, ). In epithelial cells, keratin undergoes a number of post‐transcriptional modifications, including acetylation of the N‐terminal serine (Omary et al, ).…”
Section: Post‐translational Modifications and Expression System Choicementioning
confidence: 99%
“…AcP is a small-molecule metabolite in the phosphotransacetylase (Pta)—acetate kinase (AckA) pathway, one of the basic metabolic networks in E. coli ( 19 , 21 ). In light of the recent explosion of basic research on lysine acetylation ( 22 24 ), it seems important to recall previous studies on acetylation of recombinant therapeutic proteins produced in E. coli : neurotropin-3 ( 25 ), somatotropin ( 16 ), interleukin-10 ( 26 ), interleukin-2 ( 27 ), chemokine RANTES (regulated on activation, normal T cell expressed and secreted) ( 17 ), interferon alfa ( 28 ) and gamma ( 29 ), stathmin-like subdomains ( 30 ), human basic fibroblast growth factor mutein ( 31 ) and prochymosin ( 32 ). These results support current attempts to understand the mechanism of acetylation and its implications on cell life.…”
Section: Introductionmentioning
confidence: 99%